OLAP for moving object data. (1st January 2013) - Baltzer, Oliver; Dehne, Frank; Rau-Chaplin, Andrew
In this paper, we present an OLAP framework for moving object data. We introduce a new operator GROUP_TRAJECTORIES for group-by operations on moving object data and present two implementation alternatives for computing groups of moving objects for group-by aggregation: group by overlap and group by intersection . We also present an interactive OLAP environment for resolution drill-down/roll-up on sets of trajectories and parameter browsing. We evaluate the performance of our GROUP_TRAJECTORIES operator by using generated as well as real life moving object datasets.